Therapeutic Potential of Agmatine in Essential Tremor Through Regulation of Lingo‐1 and Inflammatory Pathways - Zeynab Pirmoradi; Zahra Esmaili; Mohsen Nakhaie; Kristi A. Kohlmeier; Mohammad Shabani; Moazamehosadat Razavinasab; Mehran Ilaghi (Brain and Behavior)
ABSTRACT Purpose Essential tremor (ET) is a prevalent movement disorder, yet current therapeutic options remain limited. Emerging evidence implicates leucine‐rich repeat and immunoglobulin‐like domain‐containing protein (Lingo‐1) and neuroinflammation in the pathophysiology of ET. This study aimed to investigate whether agmatine, a biogenic amine neuromodulator attenuates tremors and modulates the expression of Lingo‐1 and proinflammatory markers in a rodent model of ET. Methods Tremor was induced in male Swiss Webster mice through intraperitoneal injections of harmaline (10 mg/kg) on Days 1, 3, and 5 of the study. During the same period, agmatine (40 mg/kg) was administered for 5 consecutive days. Behavioral assessments of tremor severity, gait, balance, muscular strength, locomotion, anxiety‐like behavior, and memory were conducted. Moreover, Lingo‐1 and interleukin (IL)‐6 gene expression was examined in the cerebellum using real‐time polymerase chain reaction (RT‐PCR). Findings Our findings demonstrated that agmatine administration significantly reduced tremors, ameliorated anxiety‐like behaviors, and attenuated harmaline‐induced locomotor deficits. At the molecular level, agmatine treatment significantly suppressed the overexpression of Lingo‐1 elicited by harmaline. Moreover, IL‐6 expression was attenuated to an extent comparable to control levels. Conclusions Collectively, this study provides the first evidence that agmatine dampens tremor severity, improves behavioral outcomes, and modulates key pathways implicated in ET pathogenesis in a rodent model. The ability of agmatine to normalize Lingo‐1 and IL‐6 expression suggests regulation of these pathways could underlie its neuroprotective action. These results suggest promise for agmatine as a prospective therapeutic agent in ET.